Steroid Hormone Levels in Recipient Amniotic Fluid in Twin–Twin Transfusion Syndrome and Their Association with Preterm Delivery - Hoffman, Mallory; Mann, Lovepreet K.; Won, Jong H.; Bergh, Eric P.; Donepudi, Roopali; Johnson, Anthony; Moise, Kenneth J.; Macpherson, Cora; Thom, Elizabeth; Mesiano, Sam; Papanna, Ramesha (American Journal of Perinatology, 2020)
Objective Preterm delivery following fetoscopic laser surgery (FLS) of twin–twin transfusion syndrome (TTTS) is associated with severe perinatal morbidity and mortality. The role of steroid hormones in amniotic fluid (AF) after FLS remains unknown.Study Design A prospective cohort study of consecutive case series of FLS for TTTS was performed from April 2012 to February 2017. Cases were divided into early (≤27 weeks) spontaneous preterm delivery (ED) and late delivery (LD; ≥34 weeks) following FLS and compared. AF supernatants were assessed for protein, estradiol, progesterone and cortisol levels (using the ELISA kit), and normalized to total protein levels to adjust for dilution.Results A total of 294 consecutive cases of FLS for TTTS in monochorionic–diamniotic twins were performed during the study period. AF was available in 44 ED patients and 50 LD patients. On logistic regression, ED was associated with higher normalized progesterone levels (odds ratio [OR]: 1.25; 95% confidence interval [CI]: 1.12–1.41), lower normalized cortisol (OR: 0.78; 95% CI: 0.64–0.96), and higher estradiol levels (OR: 1.3; 95% CI: 1.03–1.63).Conclusion Elevated AF normalized progesterone and estradiol, and lower normalized cortisol levels were associated with ED. This novel finding requires further exploration to establish the molecular mechanism operational in pregnancies complicated by TTTS to potentially prevent early preterm birth after fetal surgery.
Keywords: amniotic fluid; twin–twin transfusion syndrome; steroid hormones; progesterone; estradiol; cortisol; preterm birth; risk assessment